Dead time determination and its influence to retention index in GC system using polar capillary column - Idroes, Rinaldi; Oesman, Frida (Indonesian Journal of Pharmacy, 2011)
In this research for the determination of dead timeused a method that is mathematically calculated as iteration and linearization of the polar capillarry column  in  Gas  Chromatography  (GC)  type  DN-Wax,  by  injecting  the  homologous series  of  n-alkanes  (n-pentane  up  to  n-decane)  on  GC  system.  The  dead  time values  obtained  are  then  used  to  determine  the  Kovats  Retention  Index (Retention  Index,  RI).  The  results indicated that the  retention index  had  values of  systematic  error  those  are  more  accurate  than  the  retention  time  (tR), corrected retention time (tR') and retention factor(k'), but the retention index shows  the  value  of  random  error  slightly  larger  than  with  other  retention parameters. In this study  the average values obtained by the iteration method, the  dead  time  was  3.52  minutes  with  a  correlation  coefficient  of  0.9998.Retention  index  values  obtained  are  at  the  confidence  level  92.11%-97.06% with the systematic errors 2.04%-7.89%, while the linearization method showed the average value of the dead time 3.3 minutes witha correlation coefficient of 0.9992,  but  the  value  of  retention  index  values  obtained  show  that  the systematic error is very large.Key words:Dead time, Retention Index, Homologous Series, GC